Analysis of the Antibody Binding of Derivative MUC1 Peptides via STD NMR - Lynch, Andrew R. (My University, 2015)
This study analyzes the binding ability of the peptide GVTSAPD, an upstream sequence preceding PDTRP, as well as six derivative peptides against specific mouse MUC1 mucin monoclonal antibody (IgG1, 6A4) by Saturation Transfer Difference NMR (STD NMR) to determine the specific residue critical for antibody binding and whether analogous side chain characteristics in the derivative sequences would enhance binding.
Color poster with text and images.
Keywords: Chemistry; PDTRP; Monoclonal antibody; Antibody binding; Binding properties; Posters